RELATION BETWEEN SCREEN TIME AND SLEEPING QUALITY TO OBESITY INCIDENCE IN FEMALE ADOLESCENTS IN BANTUL DISTRICT DURING COVID-19 PANDEMIC - Miftahul Jannah Ramadhani; Faurina Risca Fauzia (Journal of Global Nutrition, 2022)
Abstract: Background: The prevalence number of obesity nutritional status in Bantul disctrict in 2018 was 13.32%. The status in adolescents is caused by various factors such as poor sleeping quality which increases screen time exposure in adolescents. Objective: The study is to investigate the relation of screen time and sleeping quality to obesity incidence in female adolescents in Bantul disctrict. Method: The study used quantitative method with case control design. The samples in the study were 13 – 18 years old female adolescents in Bantul district taken randomly by using Cluster Random Sampling technique based on sub-district resulted in 288 female adolescents data consisting of 73 groups of case and 215 control groups. The instruments of the study were questionnaire of respondents’ characteristics, QueST questionnaire, PSQI questionnaire, and antropometri measurement and the data were analyzed by using Chi-square. Result: The result of the study showed that there was no significant relation between screen time and obesity incidence in female adolescents in Bantul district (p= 0.967; OR = 1.12; 95%CI = 0.634-1.978) and there was no significant relation between sleeping quality and obesity in female adolescents in Bantul district (p= 0.672; OR = 0.98; 95%CI = 0.551-1.756). Conclusion: The study concludes that there is no significant relation between screen time and sleeping quality and obesity incidence in female adolescents in Bantul district during Covid-19 pandemic.